Penggunaan macam mulsa dan pola jarak tanam terhadap pertumbuhan dan produksi Pakchoy (Brassica rapa chinensis l.) - Heni Irawati; Endang Dwi Purbajanti; Sumarsono Sumarsono; Deden Fatchullah (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
Problems in the cultivation of plants pakchoy caused by the influence of the physical environment such as climate, wind, temperature, the intensity of solar radiation, humidity, and soil. The research aims to know types of mulch and patterns of the plant spacing for optimizing on growth and yield of pakchoy. This experiment had been conducted in the experimental field Margahayu, Balai Penelitian Tanaman Sayuran, Lembang on September-November 2016. The design of the research which used was randomized block design factorial with 9 treatment combinations and 3 replications. The first factor is “Types of Mulch”, the use of M0 (no mulch), M1 (black silver plastic mulch), and M2 (rice straw mulch). The second factor is “The Plant Spacing Patterns”, which are J0 (10x10 cm_triangle), J1 (20x20 cm_square), and J2 (30x30 cm_hexagonal). Data was analyzed with analysis of variance (ANOVA) and continued with Duncan Multiple’s Range Test (DMRT) at α=5%. The result showed that the use of black silver plastic mulch and spacing pattern of 20x20 cm (square) is a combination of the best treatment because it has the fresh weight of the canopy and the fresh weight of the roots of the most highest when compared to treatment with a combination of other, namely fresh weight of canopy 5,02 kg and weight of fresh roots 253,6 g.